Test of polystyrene toxicity on Aeromonas-sobria and staphylococcus-homini bacteria - Al-Khalidy Hiba Ibrahem; Al-Haidarey Mohammed Jawad Salih (BIO Web of Conferences, 2024)
The spread of nano-plastic particles arising from the decomposition of plastic has become a global problem because it poses a threat to primary products in food chains, and thus threatens the entire system. We tested the apparent effects on the metabolism of Gram-negative and Gram-positive bacteria after exposure to nano-plastics (nanocpolystyrene) by using carbon as an energy source. After diagnosis bacteria samples and then exposed to nanopolystyrene solution with different concentrations (200, 500 and 1000) ppm. Biology Eco Microplate (BEMP) was used to determine changes in bacteria after uptake of a carbon source. Average well-color development (AWCD) was used for data analysis, the result showed there are increase in size of bacteria and in absorption of carbon sources.